Impact of water hardness on consumers' perception of laundry washing result in five European countries - Abeliotis K.; Candan C.; Amberg C.; Ferri, Ada; Osset M.; Owens J.; Stamminger R. (Wiley, 2014)
n/a
Keywords: Marketing; Economics and Econometrics; Public Health, Environmental and Occupational Health; households surveys; textile; Applied Psychology